"RESISTANT TO THE COMPLEX STRESS FACTORS (SALT, DROUGHT, DISEASE) OF THE ”OROLBO’YI” REGION, THE YIELD OF SPRING WHEAT, THE QUALITY INDICATORS OF THE GRAIN WILL BE STABLE HIGHER. ACTIVITY IMPLEMENTED WITHIN THE FRAMEWORK OF DEVELOPMENT OF TECHNOLOGY (Intent Research Scientific Journal, 2023)
Wheat is essential to ensure a sustainable food solution around the world. In the past few years, there have been changes related to the cultivation of wheat. Climate change, drought and salinization of cultivated areas were the main reasons for this change. Therefore, in this article, a resource-efficient agrotechnology for the selection of varieties of spring wheat that are resistant to complex stress factors (salt, drought, disease) and have high grain quality indicators is presented in this article. Let's look at the conclusion of some researches. Based on the soil and climate conditions of Karakalpak, ridges with high photosynthetic productivity during the short vegetation period of spring wheat were identified. In this case, the location of the leaf surface in the area unit was determined by determining the surface of the leaf surface where photosynthesis takes place. Also, by determining the amount of chlorophyll in the leaves of varieties and ridges at different developmental stages, ridges with high photosynthetic productivity were selected. Spring wheat varieties and rows were evaluated for their nutritional value and grain quality using modern tools and equipment, and rows with high protein and gluten contents were selected. Fusarium resistance of cultivars and ridges was evaluated in laboratory and field conditions, and resistant ridges were selected.Drought resistance is an important and valuable physiological characteristic of spring wheat, and special attention was paid to this characteristic when selecting varieties suitable for the conditions of the island.